HOW DO THEIR "GROUP WORK" WORKS AS AN ACTIVE LEARNING STRATEGY OF EFL LEARNING - Sajidin Sajidin; Ashadi Ashadi (Jurnal Cakrawala Pendidikan, 2021)
The implementation of active learning in junior high schools, particularly on how students respond to it is interesting to examine. The active learning program is extensively implemented in randomly selected seven provinces, at state schools in Indonesia. This research aims to investigate the implementation of EFL (English as a Foreign Language) active learning in classroom settings and to identify how the implementation is perceived by the students. To examine the implementation, 12 classroom observations at 8 purposely selected schools were carried out. Meanwhile, to identify how the implementation was perceived by the students, a number of students were interviewed, and 12 field notes were confirmed for validation. After the data were intensively analyzed, it was found that (1) active learning was evident in most classrooms in which group work was selected as the main learning strategy; (2) strategies were employed to perform different tasks and activities within ELT (English Language Teaching) sequences; and (3) most students positively responded the implementation of active learning with some suggestion for better implementation. This research recommends that the active learning approach be implemented in EFL classrooms since it potentially promotes skills other than English language skills.